Drought stress tolerance mechanisms and their potential common indicators to salinity, insights from the wild watermelon (Citrullus lanatus): A review - Malambane, Goitseone; Madumane, Kelebogile; Sewelo, Lesego T.; Batlang, Utlwang (Frontiers in Plant Science, 2023)
Climate change has escalated the effect of drought on crop production as it has negatively altered the environmental condition. Wild watermelon grows abundantly in the Kgalagadi desert even though the environment is characterized by minimal rainfall, high temperatures and intense sunshine during growing season. This area is also characterized by sandy soils with low water holding capacity, thus bringing about drought stress. Drought stress affects crop productivity through its effects on development and physiological functions as dictated by molecular responses. Not only one or two physiological process or genes are responsible for drought tolerance, but a combination of various factors do work together to aid crop tolerance mechanism. Various studies have shown that wild watermelon possess superior qualities that aid its survival in unfavorable conditions. These mechanisms include resilient root growth, timely stomatal closure, chlorophyll fluorescence quenching under water deficit as key physiological responses. At biochemical and molecular level, the crop responds through citrulline accumulation and expression of genes associated with drought tolerance in this species and other plants. Previous salinity stress studies involving other plants have identified citrulline accumulation and expression of some of these genes (chloroplast APX, Type-2 metallothionein), to be associated with tolerance. Emerging evidence indicates that the upstream of functional genes are the transcription factor that regulates drought and salinity stress responses as well as adaptation. In this review we discuss the drought tolerance mechanisms in watermelons and some of its common indicators to salinity at physiological, biochemical and molecular level.